Determinants of medication adherence and blood pressure control among elderly hypertensive patients attending geriatric OPD at a tertiary-care hospital in a metropolitan city - Vaidya, Nitya Ashish; Pol , Sujata (International Journal Of Community Medicine And Public Health, 2025)
Background: Hypertension is a prevalent non-communicable disease (NCD) in the elderly, posing significant health risks if uncontrolled. While pharmacological interventions are effective, medication adherence remains a major barrier, particularly in low and middle-income countries like India. This study aimed to assess the level of medication adherence and blood pressure (BP) control among elderly hypertensive patients attending a geriatric outpatient department (OPD) at a tertiary-care hospital and to identify their key determinants. Methods: A cross-sectional study was conducted over two months involving 160 hypertensive patients aged 60 and above. Data were collected using a semi-structured questionnaire, 8-item Morisky medication adherence scale (MMAS-8), and medical records. BP control was categorized per 2017 AHA guidelines. Results: Among participants, 49.4% demonstrated low medication adherence, while only 26.9% achieved optimal BP control. Adherence was significantly associated with living with a spouse (p=0.043) and financial support (p=0.010). BP control was significantly linked to medication adherence (p<0.01). tobacco use (p<0.005), duration of antihypertensive treatment (p=0.0138), and number of prescribed antihypertensives (p=0.039) were indicators of poor BP control. Common challenges included difficulty accessing healthcare (51.9%) and non-availability of medications in public pharmacies (44.4%). Conclusions: The study highlighted poor adherence and suboptimal BP control in the geriatric hypertensive population. Socioeconomic dependence, lack of support, and logistical barriers significantly affect treatment outcomes. Targeted interventions like improved drug availability, home-based care, and family support systems are crucial for enhancing adherence and BP management in elderly patients.